(untitled) (Eurasian Scientific Herald, 2026)
In the late 19th and early 20th centuries, the traditional clothing of the Uzbeks in the Bukhara oasis—one of the unique historical-ethnographic regions of our Republic— developed into a distinct form. The costume complex preserved characteristics specific to various ethnic groups, reflecting the diverse aspects of the sartorial culture across the region’s ethnicities. Naturally, such features necessitate a comprehensive analysis of the traditional attire worn by the oasis population during this period. This article focuses on the study of traditional men’s clothing in the Bukhara oasis, examining the types of fabrics, ornaments, and colors utilized, as well as the symbolic meanings they conveyed. Apparel serves as a significant indicator of an individual’s gender, social background, societal status, and prestige